(untitled) (Cardiovascular Journal, 2020)
Background: Incidence of noncommunicable disease, specially cardiovascular diseases, is increasing in Bangladesh. Prevalence of risk factors in ischaemic heart disease (IHD) has been studied in different tertiary hospitals and institutes. This study was done in a secondary hospital with a patient population mainly of low socioeconomic condition and was compared with other patient groups of the country and Indian subcontinent. Methods: this cross sectional study was conducted in Manikganj Sadar Hospital from July 2019 to December 2019. All the patients admitted with the diagnosis of myocardial infarction (MI) were included. Cardiovascular risk factors, like smoking, diabetes mellitus (DM), hypertension (HTN), family history of premature cardiovascular diseases, dyslipidaemia and obesity, were evaluated among the patients. Results: This cross-sectional study showed most of the patients were in the age group of 50-59 years. 66% of the male patients and 2% of the female patients were smoker. 66% of the patients were hypertensive, 44% patients were diabetic, 28.5% patients were overweight, 60.4% patients had total cholesterol > 200mg/dl, 73.6% patients had LDL>130 mg/dl, 110 76.3% patients had HDL < 40 mg/ dl, 72.2% had triglyceride >150 mg/dl and 39% patients had family history of premature cardiovascular disease. Ninety (62.5%) patients had anterior MI, 50 (34.7%) patients had inferior MI and 4 (2.7%) patients had NSTEMI. 65 patients had no major risk factor and 57 % had three or more risk factors. Conclusion: The study population was more aged in comparison to other studies conducted in different parts of Bangladesh. Prevalence of smoking habit was lower but the prevalence of HTN, DM and dyslipidaemia were higher than the general population and other cohorts of MI patients. The prevalence of major risk factors was much higher than the general population of Bangladesh. Cardiovasc. j. 2020; 12(2): 96-101